Dismantling Cultural Prejudice: Responses to Huntington’s Thesis in the Indonesian Media - Prasetyo, Hendro (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
The ideas contained in Huntington's article,